Profiling ESL research in Colombia… a growing need? ¿Una necesidad creciente? - Uribe Enciso, Olga Lucía (Rastros Rostros, 2016)
Purpose: To increase awareness of the special importance of profiling research. Topics: indexed journals, types of reviews and research profiles. Development: Selecting a research topic could be a hard task for young researchers or experienced researchers exploring different subjects. As ESL research works have been gradually growing during the last decades, trying to have a general view of all research done on its diverse related topics is a utopian aim. Considerable efforts like handbooks, literature reviews and states of the art have been made in order to make visible and organize different types of literature texts and scientific publications by adopting any selection criteria. However, such works, although very valuable, serve very specific purposes so that they cannot give a general picture of the different published research studies on an academic arena. Research profiles can meet such a need, of course, through inclusion criteria such as time frames or geographical contexts. Also, they help research works to be known and categorized according to any parameters so that research lines can be traced and regional or national bodies or research can be acknowledged. Besides, they are the starting point of more systematic reviews and complex tasks. Conclusions: Research profiles serve different purposes such as helping researchers select research topics, track and acknowledge research works, and create research lines and set research agendas in a country.